Race, Ethnicity, and Other Factors Predicting U.S. Parents' Support for Policies to Reduce Food and Beverage Marketing to Children and Adolescents - Frances Fleming-Milici; Jennifer L. Harris; Sai Liu (Mary Ann Liebert, 2018)
Purpose: Examine parents' support for policies to reduce unhealthy food and beverage marketing to children and adolescents and identify racial, ethnic, and other sociodemographic characteristics that predict support. Methods: Online survey of U.S. parents (N=3356) with children 2?17 years of age conducted annually (2009?2012). Participants provided attitudes about food marketing to their children, including perceived negative impact and support for food marketing-related policies. Sociodemographic characteristics examined were as follows: race, ethnicity, income, gender, political orientation, and child characteristics. Results: Overall, parents agreed that food marketing negatively impacts their children's eating habits (M=6.87?2.08 out of 10) and supported food marketing-related policies (M=6.73?2.37). Perceived negative impact predicted support and was highest among black and Hispanic parents. Controlling for income and age of children in the household, Hispanic and black parents expressed highest support for policies, as did women and parents who identified as liberal or moderate in political orientation. A significant interaction between parents' political orientation and race/ethnicity indicated similarly high support among all parents, except white non-Hispanic conservative parents. Conclusion: These findings are encouraging for efforts to enact policies to address unhealthy food marketing to youth. High levels of support among parents suggest advocates should continue to engage parents in their efforts. Findings also suggest that families of color would welcome policies limiting unhealthy food marketing to youth in their communities. Issues of targeted marketing and disproportionate exposure to unhealthy food marketing by black and Hispanic youth may be incorporated into campaigns to address food justice and health inequities in communities of color.